Reading Disability and Adult Attained Education and Income: Evidence From a 30-Year Longitudinal Study of a Population-Based Sample. (July 2014) - McLaughlin, Margaret J.; Speirs, Katherine E.; Shenassa, Edmond D.
This study examined the impact of childhood reading disability (RD) on adult educational attainment and income. Participants' ( N = 1, 344) RD was assessed at age 7, and adult educational attainment and income were assessed in midlife using categorical variables. Participants with RD at age 7 were 74% (95% CI: 0.18, 0.37) less likely to attain a higher level of education and 56% (95% CI: 0.32, 0.61) less likely to attain a higher level of income as an adult than participants with average or above reading achievement at age 7. Attained education was found to mediate the relationship between RD and attained income.